The survivors : a story of war, inheritance, and healing - Frankel, Adam P (Harper, an imprint of HarperCollinsPublishers, 2019)
"A memoir of family, the Holocaust, trauma, and identity, in which Adam Frankel, a former Obama speechwriter, must come to terms with the legacy of his family's painful past and discover who he is in the wake of a life-changing revelation about his own origins. Adam Frankel's maternal grandparents survived the Holocaust and built new lives, with new names, in Connecticut. Though they tried to leave the horrors of their past behind, the pain they suffered crossed generational lines--a fact most apparent in the mental health of Adam's mother. When Adam sat down with her to examine their family history in detail, he learned another shocking secret, this time one that unraveled Adam's entire understanding of who he is. In the midst of piecing together a story of inherited familial trauma, Adam discovered he was only half of who he thought he was, knowledge that raised essential questions of identity. Who was he, if not his father's son? If not part of a rich heritage of writers and public servants? Does it matter? What defines a family's bonds? What will he pass on to his own children? To rewrite his story in truth and to build a life for his own young family, Adam had to navigate his pain to find answers and a way forward. Throughout this journey into the past, his family's psyche, and his own understanding of identity, Adam comes to realize that while the nature of our families' traumas may vary, each of us is faced with the same choice. We can turn away from what we've inherited--or, we can confront it, in the hopes of moving on and stopping that trauma from inflicting pain on future generations. The stories Adam shares with us in The Survivors are about the ways the past can haunt our future, the resilience that can be found on the other side of trauma, and the good that can come from things that are unspeakably bad"--